Evaluation of commercial product in the foliar fertilization of Brachiaria - Sousa, Victor Luke de Castro; Silva, Higgor Henrique Caldas; Freire, Ana Izabella; Araújo, Nicolas Oliveira de (Seven Editora, 2023)
Knowing about the benefits of a good bioactivator on forage cultivation is extremely important to obtain more satisfactory results. As a result, this study aims to know the the performance of foliar fertilization with the product Raizal® in forages of the genus Brachiaria in Tocantins, making research on the action of this product in forage crops necessary both for the improvement of new plantations and in the increase of regrowth power for the recovery of degraded pastures. The study will be carried out in the field at Centro Universitário Presidente Antônio Carlos, where experimental posts will be used to determine the productivity of grass with the use of Raizal® foliar fertilizer in different doses, following the dose indicated by the manufactures, half of the dose anda the dosage higher than recommended, as well as a sample without fertilizer application so that the effects of the Raizal® product on the plants used in the experiment can be demonstrated through greaterperformance and productivity according to the amount of product applied. DOI:https://doi.org/10.56238/uniknowindevolp-047